VIBRATION EQUIPMENT FOR CLEANING LIQUIDS FROM SOLID INCLUSIONS: CURRENT STATE AND PROMISING DIRECTIONS OF DEVELOPMENT - SVIASHCHUK, YURII; ZAHNITKO, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides a comprehensive review of the current state, technical characteristics and development prospects of vibration equipment for cleaning liquids from solid inclusions. It is shown that the growing need of industry for highly efficient, energy-saving and environmentally friendly technologies leads to the active introduction of vibration separation methods. The main types of vibration systems are classified - mesh, ultrasonic, electromagnetic, piezoelectric, membrane and cavitation units. For each type, characteristic frequency ranges, cleaning efficiency levels and specific areas of application in water treatment, chemical, pharmaceutical, food and petrochemical industries are given. Special attention is paid to low-frequency vibration cavitators, capable of providing liquid processing under increased pressure, which allows to intensify cavitation processes, increase disinfection efficiency and reduce energy consumption. The technical parameters of different types of installations were analyzed - oscillation amplitude, productivity, operating pressure range, service life. It was proven that the use of vibration technologies reduces the duration of liquid processing, ensuring stable results even with variable physicochemical properties of the medium. Innovative directions of industry development were highlighted: integration of IoT systems for automatic control of process parameters, use of nanostructured membranes and smart materials, creation of hybrid and modular systems that combine different separation principles. The main technical challenges associated with fatigue strength of structures, stabilization of vibration modes and prevention of filter clogging were identified. It was concluded that vibration cleaning methods are a promising direction for the development of energy-efficient and high-performance separation technologies for a wide range of industries.